Event dynamics and injury reconstruction of a zip-line incident using MADYMO software: a case study. (2017) - Desmoulin, Geoffrey Thor; Doslikova, Katerina
GTD Engineering was retained to perform a biomechanical investigation of a zip-line incident involving head and neck injuries sustained by a female patron. Resources limited a full-scale reconstruction of the incident; hence a MADYMO (MAthematical DYnamic MOdels) software model was used in its place. The aim of the study was to assess the model's dynamics and injury responses as well as provide a description of its development. The model was validated using (a) a sensitivity analysis, (b) the actual injuries sustained during the incident as confirmed by medical records and (c) eyewitness accounts of the event. A description of key time points, how they were reconstructed and the likelihood of injuries sustained during each are provided. The model created using MADYMO proved to be an accurate tool to reconstruct the incident, including event kinematics, kinetics and injury responses.